Structural and Optical Investigations of Radiation Damage in Transparent PET Polymer Films. (21st March 2011) - Prasad, Shiv Govind; De, Abhijit; De, Udayan
Abstract : Effects of gamma irradiation at different doses up to 135 kGy on polyethylene terephthalate (PET) polymer films have been investigated by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and ultraviolet-visible (UV-VIS) spectroscopy. From XRD analysis, it was found that even at a high dose of gamma irradiation of 135 kGy, crystallinity of the PET samples remain unchanged. However, the FTIR peak at 871 cm −1 (depicting C–H bending mode of out-of-plane vibration) and another at 1303 cm −1 (representing C–H bending mode of in-plane vibration) disappear for gamma-irradiated PET. In this study, it has also been found that γ -irradiation in air enhances the optical absorption in the wavelength region 320–370 nm. This has been attributed to free radicals being produced in the polymer by the γ -radiation. Further, the free radicals react with oxygen of air to form carbonyl group and hydroxyls. With increasing γ -dose, there is a red shift of the UV—near visible cutoff for PET. XRD and FTIR observations on γ -damage have been correlated.